Memadukan Konsep Kecerdasan Intelektual, Emosional, Spiritual dan Ruhaniah Dalam Proses Pendidikan - Muzhoffar Akhwan (EL-TARBAWI, 2002)
The substation of Education is child’s growth proceed in order to independent in the future to solution of their life problems. In order to of the  child's education can be succeed. That's way educator (parents and the teacher) must understand the child based potential is adult tendentious  imitate. Education through example and to accustom oneself of behavior  and word are relevant to children period. The educational method with model (al-tarbiyah bi al-qudwah) and good wise and right can be impressed at child whom finally will get used to  behavior daily. For strengthen imitate push which good and right can be  used reward (tsawaab, in Islamic educational system should be highly motivated by this reward. Punishment (iqaab) or hit United State of  America strenphens in order to not to be adopted. In the Islamic System  corporal punishment is recognized and regarded United State of America  as an effective means of correction.  Remind of parents and that of teacher are important, that's way between  parents education and the teacher must help each others not contradictive about the content of any curriculum which are taught or behavior which  showed to the children.Key Word: Child's Education, islamic Education System